2014
DOI: 10.1124/dmd.114.060319
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of Near Infrared Fluorescent Labeling of Monoclonal Antibodies as a Tool for Tissue Distribution

Abstract: The pharmacokinetic (PK) behavior of monoclonal antibodies (mAbs) is influenced by target-mediated drug disposition, off-target effects, antidrug antibody-mediated clearance, and interaction with fragmentcrystallizable domain (Fc) receptors such as neonatal Fc receptor. All of these interactions hold the potential to impact mAb biodistribution. Near infrared (NIR) fluorescent probes offer an approach complementary to radionuclides to characterize drug disposition. Notably, the use of IRDye800 (IR800; LI-COR, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 21 publications
3
39
0
Order By: Relevance
“…At longer times, the beta phase clearance diverges significantly, indicating 800CW altered the pharmacokinetics of the antibody. These data agree with Conner et al, 6 where the clearance of a different antibody–800CW conjugate showed faster clearance at a similar DoL of 1.5. At a 0.3 DoL, however, both Tras-800CW and Bev-800CW showed similar clearance over the first several days, and only after 4 days does the clearance diverge significantly.…”
Section: Resultssupporting
confidence: 92%
“…At longer times, the beta phase clearance diverges significantly, indicating 800CW altered the pharmacokinetics of the antibody. These data agree with Conner et al, 6 where the clearance of a different antibody–800CW conjugate showed faster clearance at a similar DoL of 1.5. At a 0.3 DoL, however, both Tras-800CW and Bev-800CW showed similar clearance over the first several days, and only after 4 days does the clearance diverge significantly.…”
Section: Resultssupporting
confidence: 92%
“…Another study concluded that IRDye800 in a low dye/protein labeling ratio does not significantly alter the pharmacokinetics of cetuximab, which has a relatively short half-life at ASPET Journals on May 9, 2018 dmd.aspetjournals.org (2.5 days) (Zinn et al, 2015). In contrast, altered mAb pharmacokinetics in plasma and tissues were observed for bevacizumab, cetuximab, and mouse monoclonal IgG1 (8C2), featuring increased plasma elimination and liver uptake (Cohen et al, 2011;Conner et al, 2014). We also observed the apparent increased plasma elimination as well as enhanced liver and kidney uptake of etanercept measured by fluorescence.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of labeling (DOL) was kept below 1 for most dyes to minimize the presence of multiple dyes on a single antibody. For in vivo work, this can have a strong impact on distribution [21]. …”
Section: Discussionmentioning
confidence: 99%